PRELP secreted from mural cells protects the function of blood brain barrier through regulation of endothelial cell-cell integrity - Davaapil, Hongorzul; Hopkins, Jack; Bonnin, Nadia; Papadaki, Vasiliki; Leung, Alex; Kosuge, Hirofumi; Tashima, Takumi; Nakakido, Makoto; Sekido, Ryohei; Tsumoto, Kouhei; Sagoo, Mandeep S.; Ohnuma, Shin-Ichi (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Proline/arginine-rich end leucine-rich repeat protein (PRELP), is a small secreted proteoglycan expressed by pericytes and vascular smooth muscle cells surrounding the brain vasculature of adult mouse. Methods: We utilised a Prelp knockout (Prelp−/−) mouse model to interrogate vasculature integrity in the brain alongside performing in vitro assays to characterise PRELP application to endothelial cells lines. Our findings were supplemented with RNA expression profiling to elucidate the mechanism of how PRELP maintains neurovasculature function. Results:Prelp−/− mice presented with neuroinflammation and reducedneurovasculature integrity, resulting in IgG and dextran leakage in the cerebellum and cortex. Histological analysis of Prelp−/− mice revealed reducedcell-cell integrity of the blood brain barrier, capillary attachment of pericytes andastrocyte end-feet. RNA-sequencing analysis found that cell-cell adhesion andinflammation are affected in Prelp−/− mice and gene ontology analysis as well as gene set enrichment analysis demonstrated that inflammation related processes and adhesion related processes such as epithelial-mesenchymal transition and apical junctions were significantly affected, suggesting PRELP is a regulator of cell-cell adhesion. Immunofluorescence analysis showed that adhesion junction protein expression levels of cadherin, claudin-5, and ZO-1, was suppressed in Prelp−/− mice neurovasculature. Additionally, in vitro studies revealed that PRELP application to endothelial cells enhances cell-cell integrity, induces mesenchymal-endothelial transition and inhibits TGF-β mediated damage to cell-cell adhesion. Discussion: Our study indicates that PRELP is a novel endogenous secreted regulator of neurovasculature integrity and that PRELP application may be a potential treatment for diseases associated with neurovascular damage.